2018
DOI: 10.1115/1.4040318
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Skeletal Muscle Stress and Intramuscular Pressure: A Whole Muscle Active–Passive Approach

Abstract: Clinical treatments of skeletal muscle weakness are hindered by a lack of an approach to evaluate individual muscle force. Intramuscular pressure (IMP) has shown a correlation to muscle force in vivo, but patient to patient and muscle to muscle variability results in difficulty of utilizing IMP to estimate muscle force. The goal of this work was to develop a finite element model of whole skeletal muscle that can predict IMP under passive and active conditions to further investigate the mechanisms of IMP variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…While determining material properties of aponeurosis can provide quantitative insight into muscle-tendon unit function, they are most useful in developing and employing computational models of the musculoskeletal system. Approaches to model muscle-tendon units range from classical Hill-type models (Ackland et al, 2012), more geometrically complex finite element simulations (Tsui et al, 2004;Wheatley et al, 2018), and larger scale simulations of whole human movement (Rajagopal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While determining material properties of aponeurosis can provide quantitative insight into muscle-tendon unit function, they are most useful in developing and employing computational models of the musculoskeletal system. Approaches to model muscle-tendon units range from classical Hill-type models (Ackland et al, 2012), more geometrically complex finite element simulations (Tsui et al, 2004;Wheatley et al, 2018), and larger scale simulations of whole human movement (Rajagopal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although a direct analysis of IDP has not yet been carried out, a positive correlation between fluid pressure and passive strain has already been demonstrated in nerves and muscles. [93][94][95][96] For example, intraneural pressure in the sciatic nerve increases from 8 mm Hg to 56 mm Hg during a straight leg raise. 95 Theoretical and experimental studies have also shown that fluid pressure increases strongly when hydraulic permeability of the ECM decreases, as this is associated with a higher resistance to fluid flow.…”
Section: Increased Intratendinous Resting Pressure Impairs Vascularis...mentioning
confidence: 99%
“…Typically, the tissue is modeled as a saturated poroelastic material that is divided into solid and fluid subvolumes. At the local scale (about 1 cm) poroelastic methods have been employed in the contexts of solid tumors 27 33 , injection sites 34 39 , under indentation probes 40 – 42 , near the edge of a compression wraps and in normal tissues 43 47 . The local models often include capillary permeability and lymphatic clearance, but over such relatively short distances, gravity has little opportunity to build significant hydrostatic pressures.…”
Section: Introductionmentioning
confidence: 99%